Blood concentrations of small extracellular vesicles are determined by a balance between abundant secretion and rapid clearance. Issue 1 (1st January 2020) - Matsumoto, Akihiro; Takahashi, Yuki; Chang, Hsin-Yi; Wu, Yi-Wen; Yamamoto, Aki; Ishihama, Yasushi; Takakura, Yoshinobu
ABSTRACT: Small extracellular vesicles (sEVs) are important mediators of cell–cell communication with respect to diverse physiological processes. To further understand their physiological roles, understanding blood sEV homoeostasis in a quantitative manner is desired. In this study, we propose novel kinetic approaches to estimate the secretion and clearance of mouse plasma–derived sEVs (MP-sEVs) based on the hypothesis that blood sEV concentrations are determined by a balance between the secretion and clearance of sEVs. Using our specific and sensitive sEV labelling technology, we succeeded in analysing MP-sEV clearance from the blood after intravenous administration into mice. This revealed the rapid disappearance of MP-sEVs with a half-life of approximately 7 min. Moreover, the plasma sEV secretion rate, which is presently impossible to directly evaluate, was calculated as 18 μg/min in mice based on pharmacokinetic (PK) analysis. Next, macrophage-depleted mice were prepared as a model of disrupted sEV homoeostasis with retarded sEV clearance. MP-sEV concentrations were increased in macrophage-depleted mice, which probably reflected a shift in the balance of secretion and clearance. Moreover, the increased MP-sEV concentration in macrophage-depleted mice was successfully simulated using calculated clearance rate constant, secretion rate constant and volume of distribution, suggesting the validity of our PK approaches. These results demonstrate that blood sEV concentration homoeostasis can be explained by the dynamics of rapid secretion/clearance.